Comparison of pulmonary vein isolation using cryoballoon, high-power short-duration, and conventional radiofrequency ablation for atrial fibrillation: a propensity score-weighted study - Park, Hanjin; Park, Je-Wook; Kim, Daehoon; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Joung, Boyoung; Lee, Moon-Hyoung; Hwang, Chun; Pak, Hui-Nam (Frontiers in Cardiovascular Medicine, 2023)
Abstract Background: The comparative efficacy, safety, and heart rate variability (HRV) parameters after pulmonary vein isolation using cryoballoon (Cryo-PVI), high-power short-duration (HPSD-PVI), and conventional radiofrequency ablation (conventional-PVI) for atrial fibrillation (AF) is unclear. Methods: In this propensity score-weighted, retrospective analysis of a single-center cohort, we analyzed 3,395 patients (26.2% female, 74.5% paroxysmal AF) who underwent AF catheter ablation without an empirical left atrial ablation. Procedural factors, recurrence rates, complication rates, and the post-procedural heart rate variability (HRV) parameters were compared across the Cryo-PVI (n=625), HPSD-PVI (n=748), and conventional-PVI (n=2,022) groups. Results: Despite shortest procedural time in the Cryo-PVI group (74 min for Cryo-PVI vs. 104 min for HPSD-PVI vs. 153 min for conventional-PVI, p < 0.001), the major complication (p = 0.906) and clinical recurrence rates were similar across the three ablation groups (weighted log-rank, p = 0.824). However, Cryo-PVI was associated with a significantly lower risk of recurrent AF in patients with paroxysmal AF (weighted hazard ratio [WHR] 0.57, 95% confidence interval [CI] 0.37-0.86) whereas a higher risk of recurrent AF in patients with persistent AF (WHR 1.41, 95% CI 1.06-1.89, p for interaction < 0.001) compared with the conventional-PVI group. In the subgroup analysis for the HRV, Cryo-PVI had the highest whereas HPSD-PVI group had the lowest low-frequency to high-frequency ratio at one-year post-procedure (p < 0.001). Conclusions: Cryo-PVI had better rhythm outcomes in patients with paroxysmal AF but worse rhythm outcomes in those with persistent AF, and a higher long-term post-procedural sympathetic nervous activity and sympatho-vagal balance compared with conventional-PVI.